2020
DOI: 10.2147/ott.s234517
|View full text |Cite
|
Sign up to set email alerts
|

<p>Repression of PCGF1 Decreases the Proliferation of Glioblastoma Cells in Association with Inactivation of c-Myc Signaling Pathway</p>

Abstract: Glioblastoma (GBM) is the most common primary brain tumor with a poor therapeutic outcome. Polycomb group factor 1 (PCGF1), a member of the PcG (Polycomb group) family, is highly expressed in the developing nervous system of mice. However, the function and the mechanism of PCGF1 in GBM proliferation still remain unclear. Methods: Knockdown of PCGF1 was performed in U87 GBM cell by shRNA strategy via lentivirus vector. MTT assay, colony formation assays, and flow cytometry were used to measure the properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…We further predicted the expression of PCGF1 in various human cancers through the GEDS database and found that PCGF1 was generally more highly expressed in tumour tissue than in normal tissues. Studies also showed that PCGF1 could promote cell cycle progression and proliferation in HeLa and SH-SY5Y tumour cells [ 21 ]; PCGF1 is highly expressed in glioma cells and stem cell-like glioma cells (SLCs) and promotes the U87 glioma cell proliferation, colony formation [ 34 ] and self-renewal abilities of SLCs [ 22 ]. Herein, our results indicated that PCGF1 was markedly upregulated in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further predicted the expression of PCGF1 in various human cancers through the GEDS database and found that PCGF1 was generally more highly expressed in tumour tissue than in normal tissues. Studies also showed that PCGF1 could promote cell cycle progression and proliferation in HeLa and SH-SY5Y tumour cells [ 21 ]; PCGF1 is highly expressed in glioma cells and stem cell-like glioma cells (SLCs) and promotes the U87 glioma cell proliferation, colony formation [ 34 ] and self-renewal abilities of SLCs [ 22 ]. Herein, our results indicated that PCGF1 was markedly upregulated in colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the function of PCGF1 mostly focuses on stem cell self-renewal and embryonic development [ 18 , 20 ]. With the in-depth study of PCGF1, the role of PCGF1 in tumour occurrence and development has been gradually revealed [ 22 , 34 ]. Canonically, PCGF1 is characterized as a transcriptional repressor that interacts with KDM2B, RING1B and other components to jointly regulate gene transcription and expression [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCGF6 participates in the maintenance of embryonic stem cells (ESC) identity by modulating expression of the core ESC regulators Oct4, Sox2, and Nanog (34). Concerning the roles of PCGF1 in cancers, several studies have shown that PCGF1 is implicated in the regulation of CSC self-renewal via targeting stemness markers (9,10,29), and promotes the proliferation of cancer cells by suppressing CDK inhibitors or activating oncoprotein c-Myc (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that PCGF1 positively regulates CSC self-renewal by repressing the synthesis of all-trans retinoic acid (10). In addition, PCGF1 is also regarded as a cell growth regulator that promotes cell proliferation by repressing c-cyclin dependent kinase inhibitor 1A (CDKN2A, also known as p21Waf1/Cip1), or activating the c-Myc signaling pathway in malignant tumors (11,12). PCGF1 plays important roles in cell stemness and proliferation in tumors, but the relationship between PCGF1 and clinical prognosis, as well as other underlying functions of PCGF1, especially in tumor immunity, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Among the various PCGF proteins, PRC1 is typically involved in canonical polycomb repressive complex 1 (cPRC1) and non-canonical polycomb repressive complex 1 (ncPRC1) ( 16 , 19 ). As one of the members of the PRC1, PCGF1 is a protein coding gene and is overexpressed in the developing nervous system ( 15 ). The RING finger domain of PCGF1 is 93% homologous to Bmi1 (PCGF4) ( 13 , 18 , 20 ).…”
Section: Introductionmentioning
confidence: 99%